The Study of Surah Al-Ma’un as a Foundation for Strengthening Social Care Character in Islamic Educational Institutions - M. Munif Munif (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This research is motivated by the problem of low social care character among students, which is reflected in declining empathy, a lack of concern for others, and the strengthening of individualistic attitudes within educational environments. This condition indicates the need for a character-strengthening model rooted in Qur’anic values, particularly Surah Al-Ma’un, which strongly emphasizes social awareness. The purpose of this study is to analyze the social values contained in Surah Al-Ma’un and their relevance as a foundation for strengthening social care character in Islamic educational institutions. This research employs a literature study method by collecting, analyzing, and synthesizing literature related to character education concepts, Qur’anic values, and interpretations of Surah Al-Ma’un. The results show that Surah Al-Ma’un contains values of empathy, prohibition of neglecting orphans, encouragement to support the poor, and prohibition of showing off in worship—all of which are relevant to developing social care character. The internalization of these values can be implemented through Islamic Religious Education (PAI), teacher role-modeling, habituation, and social activities in schools. The implications of this study indicate that Islamic educational institutions need to systematically integrate the values of Surah Al-Ma’un into their curriculum and learning practices to build a stronger culture of social concern among students.